Isolation of antibiotic resistant salmonella spp. from fresh vegetables collected from local wet markets of Dhaka city - Ritu, Mahmuda Akter; Bushra, Anika (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.